(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Artificial Intelligence (AI) is rapidly transforming the nature of work across industries by automating routine tasks, improving productivity, and enabling data-driven decision-making. While AI contributes to efficiency and innovation, it also raises concerns related to job displacement, skill obsolescence, and workforce uncertainty. This study examines the impact of AI on employment trends and workforce dynamics across selected industries in India. Data collected from 150 employees working in IT, manufacturing, and service sectors reveal that AI simultaneously leads to job displacement and job creation, with a significant increase in demand for advanced skills. Correlation analysis shows a strong positive relationship between AI adoption and productivity, skill requirements, and employment restructuring. The study concludes that AI should be viewed not as a threat but as a catalyst for workforce transformation, provided organizations invest in reskilling and ethical AI adoption